Meningkatkan Hasil Belajar IPS Menggunakan Kombinasi Model Problem Based Learning, Contextual Teaching Learning, Dan Picture And Picture Siswa Kelas 4 SDN HANDIL BAKTI - Muhammad Munaiya; Susilawaty (CV. ITTC INDONESIA, 2024)
This study uses Classroom Action Research (CAR). The subjects of the study were fourth-grade students of SDN Handil Bakti in the academic year 2023/2024, totaling 30 students comprising 16 boys and 14 girls. The aim of this research is to describe the activities of teachers and students, and to analyze the learning outcomes of students in implementing Social Studies (IPS) using a combination of Problem Based Learning, Contextual Teaching Learning, and Picture & Picture models in the fourth grade of SDN Handil Bakti. The results of the research revealed that the teacher's activities in the first meeting were classified as Good, reaching Very Good by the third meeting. Student activities, initially categorized as Less Active in the first meeting, significantly increased to Very Active by the third meeting. Consequently, this impacted the learning outcomes, where the classical completeness in the first meeting was classified as Not Complete, progressing to Complete by the third meeting.